ответ: х=5 ; у=2.
Пошаговое объяснение:
А)
4х-у=18 (1) уравнение
2х+у=12 (2). уравнение
Складываем уравнения.
6х=30.
х=5 .
у=12-2*5=2 из (2) уравнения.
Б)
х+3у=23 (1) уравнение
5х-9у=-53. (2). уравнение
Умножим (1) уравнение на 3.
3х+9у=69
5х-9у=-53.
Складываем.
8х=16.
х=2.
Из (1) уравнения
у=(23-х)/3=(23-2)/3=7.
В)
1/2 х-2/3 у=3 (1) уравнение
х-3у=1 (2). уравнение
Преобразуем (1) уравнение
3х-4у=18 (1)
х-3у=1 (2)
Умножим (2) уравнение на (-3)
3х-4у=18
-3х+9у=-3.
Сложим.
5у=15.
у=3.
Из (2) уравнения находим х.
х=1+3*3=10.
ответ: х=10; у=3.
Пошаговое объяснение:
1) 2/3 * 2 = 2*2 / 3 = 4/3 = 1 1/3
2) 3 * 2/7 = 3*2 / 7 = 6/7
3) 2/3 * 6/4 = 2*6 / 3*4 =
12/12 = 1
4) 10/60 * 100/25 = 1/6 * 4 = 1*4 / 6 = 4/6 = 2/3